2018
DOI: 10.1109/tgrs.2018.2805286
|View full text |Cite
|
Sign up to set email alerts
|

Generative Adversarial Networks for Hyperspectral Image Classification

Abstract: A Generative Adversarial Network (GAN) usually contains a generative network and a discriminative network in competition with each other. The GAN has shown their capability in a variety of applications. In this paper, the usefulness and effectiveness of GAN for classification of hyperspectral images (HSIs) is explored for the first time. In the proposed GAN, a convolutional neural network (CNN) is designed to discriminate the inputs and another CNN is used to generate so-called fake inputs. The aforementioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
290
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 607 publications
(291 citation statements)
references
References 42 publications
1
290
0
Order By: Relevance
“…Along with the promising performance that CNNs have achieved in the hyperspectral domain [35], [15], [16], [17], there are several directions of research that can be construed as open problems on this dataset: 1) Radiance or Reflectance: We compared the performance of U-Net-m-SE on the radiance and reflectance sets of images and obtain an mIOU of nearly 5 points less when using reflectance (reflectance-mIOU: 69.90 vs radiance-mIOU: 75.35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the promising performance that CNNs have achieved in the hyperspectral domain [35], [15], [16], [17], there are several directions of research that can be construed as open problems on this dataset: 1) Radiance or Reflectance: We compared the performance of U-Net-m-SE on the radiance and reflectance sets of images and obtain an mIOU of nearly 5 points less when using reflectance (reflectance-mIOU: 69.90 vs radiance-mIOU: 75.35).…”
Section: Discussionmentioning
confidence: 99%
“…Hao et al designed a twostream architecture, where stream1 used a stacked denoising autoencoder to encode the spectral values of each input pixel of a patch and stream2 used a CNN to process the patch's spatial features [15]. Zhu et al used a generative adversarial networks (GANs) to create robust classifiers of hyperspectral signatures [16]. Recently, Roy et al proposed using a 3D-CNN followed by a 2D-CNN to learn better abstract level representations for HSI scenes [17].…”
Section: B Semantic Segmentationmentioning
confidence: 99%
“…They showed that their 3D CNN models were able to achieve a better classification rate than the standard 2D CNN models. He et al [156] and Zhu et al [157] applied GAN to HSI classification, who showed that GAN gave better performance than the traditional CNN when training data was limited.…”
Section: Earth Data Classificationmentioning
confidence: 99%
“…A generative adversarial network (GAN) is a deep learning architecture in which two neural networks compete against each other in a zero‐sum game framework . Specifically, a GAN model consists of two parts: a generator and a discriminator.…”
Section: Introductionmentioning
confidence: 99%
“…A generative adversarial network (GAN) 43 is a deep learning architecture in which two neural networks compete against each other in a zero-sum game framework. [44][45][46][47][48][49] Specifically, a GAN model consists of two parts: a generator and a discriminator. In the training stage of a GAN model, the samples produced by the generator, together with real images, serve as inputs to the discriminator.…”
Section: Introductionmentioning
confidence: 99%